Experience of respectful maternity care and its determinants among women and midwives - K. A., Ansiya; Subrahmanyam, Namitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Respectful Maternity Care (RMC)is an approach to care that highlight the fundamental rights of women, new-borns, and families, and that promotes impartial access to evidence‐based care while recognizing the unique needs of both women and new-borns. Methods: In a cross-sectional analytical study assessing experience of Respectful Maternity Care and its determinants among women and midwives, 33 midwives and 99 postnatal mothers from a tertiary care hospital, in central Kerala were enrolled in the study using convenience sampling. Structured and standardized questionnaire were used to collect data. Results: The mean score of overall experience on RMC was higher among midwives (68.76) as compared to women (60.59). The domain wise comparison of RMC experiences revealed that midwives’ scores on providing comfort (92.8) and participatory care (85.7) were significantly (p<0.001) higher as compared to score obtained by women for providing comfort (75) and participatory care (71.4). The mean score for the factor 3 (Mistreatment) was same for both groups which was found to be the least (80). The study revealed significant disparity between the perception of caring experience on RMC among midwives and women. Conclusions: More evidence-based interventions need to be implemented to ensure agreement on quality of RMC care provided by midwives and care received by women in the intrapartum care unit.